Typical and Atypical Antipsychotic induced weight gain (AIWG) and its metabolic correlates among male forensic inpatients in Cape Town, South Africa - Nadvi, Syed (Department of Psychiatry and Mental Health, 2025)
Antipsychotic induced weight gain (AIWG) is a well described phenomenon in psychiatric literature. However, there is a dearth of information on its prevalence in patients admitted to forensic units. Forensic inpatients are at heightened risk for weight gain and Metabolic Syndrome (MetS) due to long term exposure to antipsychotic (AP) medications. Aim: We aimed to describe and compare the weight changes and metabolic profile of male forensic state patients exposed to typical and atypical AP and identify modifiable risk factors, enabling us to determine if there is a significant difference between typical and atypical AP in the development of weight gain and MetS. Method: The study design was a retrospective folder review. The populations consisted of 75 male forensic state patients, stratified into those prescribed only atypical antipscyhotics (AAP) and those prescribed only typical antipsychotics (AP). The metabolic parameters on admission (From 2017) and at follow up (Up to 2022) were documented. Ethics approval was granted by the University's Human Research Ethics Committee (HREC). Results: An average increase of 17.7 kg weight from admission to follow-up across both groups, with a 35.1% and 25.1% increase in the atypical and typical groups respectively. There was a 46.2% increase in the incidence of MetS in the AAP group, compared to 40.1% in the typical AP group. Patients on AAP had a significantly larger absolute and % change in weight than those on typical AP (p= 0.01/0.025 respectively). Conclusion: This study is the first in a forensic unit in South Africa to show that all AP are associated with weight gain and MetS, with AAP having a significantly larger change in weight (p=0.01) . Further studies with larger sample sizes in other forensic state patient populations can be done to confirm associations found in our study.